Excel® 2013 formulas - Walkenbach, John (Mr. Spreadsheet's bookshelf., 2013)
Explains how to get the most out of Excel 2013's formulas, covering such topics as worksheet functions, named cells and ranges, array formulas, megaformulas, debugging, and creating custom functions with VBA.